Recent advances in renewable energy technology for the energy transition - Østergaard, Poul Alberg; Duic, Neven; Noorollahi, Younes; Kalogirou, Soteris A. (My University, 2021)
This article presents some of the main findings from the SDEWES conferences of 2021 within the field of renewable energy. More specifically, results are summarized and contextualised within solar energy and thermal comfort, wind power resource assessment, and biogas and biomass resources and technology. The two last sections deal more broadly with energy systems and energy systems transition issues; the systems analyses used to design complex renewable energy systems and the investment strategies and barriers associated with the transition.
Keywords: Compressed Air Energy Storage; Electricity Storage; Arbitrage